2022
DOI: 10.18632/aging.203905
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated exosome-associated gene FGF9 as a novel diagnostic and prognostic target for ovarian cancer and its underlying roles in immune regulation

Abstract: Exosome has been demonstrated to be secreted from cells and seized by targeted cells. Exosome could transmit signals and exert biological functions in cancer progression. Nevertheless, the underlying mechanisms of exosome in ovarian cancer (OC) have not been fully explored. In this study, we wanted to explore whether Fibroblast growth factor 9 (FGF9), as an exosome-associated gene, was importantly essential in OC progression and prognosis. Firstly, comprehensive bioinformatics platforms were applied to find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Based on previous studies, we obtained 120 exosome-related genes ( Wang et al, 2021 ; Xu et al, 2022 ). We obtained 40 prognosis-related exosomal genes through univariate Cox regression analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, we obtained 120 exosome-related genes ( Wang et al, 2021 ; Xu et al, 2022 ). We obtained 40 prognosis-related exosomal genes through univariate Cox regression analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, a total of 120 exosome related genes are shown in Supplementary Table S1 ( Wang et al, 2021 ; Xu et al, 2022 ). Pearson correlation was used to explore the relationship between lncRNAs and exosome-related genes.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the differently expressed genes (DEGs) between the normal liver tissues and LIHC were screened with the following criteria: P value <0.01 and |logFC| > 1 ( Table 1 ). Next, Venn plots were employed to identify the co-DEGs among the exosome-associated gene dataset (Supplementary Table 1 ) [ 24 ] and the above-mentioned GEO datasets. After then, Xiantao Xueshu [ 25 ], TNMplot [ 26 ], and UALCAN [ 27 ] were used to confirm the downregulated expression levels of ENPP1 in LIHC tissues.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the levels of miR-200a, miR-200b, miR-200c, and miR-1290 were increased in the ascites of OC patients, and the level of miR-200b was associated with overall survival rate [ 38 ]. As an EV-associated gene, the expression of fibroblast growth factor 9 (FGF9) in ovarian epithelial tissue was lower than that in normal ovarian tissue, and the downregulated FGF9 showed good prognostic value in patients with OC [ 21 ]. The plasma EV-derived fragile site-associated tumor suppressor (FATS) was significantly decreased in OC patients; meanwhile, low levels of plasma EVs-derived FATS were closely associated with the Federation International of Gynecology and Obstetrics (FIGO) stage III/IV, high grade, ascites, elevated CA-125, and lymph node metastasis and prognosis of OC patients [ 22 ].…”
Section: Progress Of the Research Into Evs In The Diagnosis And Treat...mentioning
confidence: 99%